Lysosome Sensing Is a Key Mechanism in Leishmania Intracellular Development - Zilberstein, Dan (Frontiers in Microbiology, 2021)
Phagolysosomes of macrophages are the niche where the parasitic protozoan Leishmania resides and causes human leishmaniasis. During infection, this organism encounters dramatic environmental changes. These include heat shock (from 26⁰C in the vector to 37⁰C in the host), acidic pH typical to the lysosome and nutrient availability. Leishmania cells developed ways to sense the lysosome-specific environment (acidic pH and body temperature) as means of recognition and subsequently, initiation of differentiation into the intracellular form. This review provides an update on the molecular mechanisms of Leishmania sensing of phagolysosome content.